Usabivalid Tool: Evaluating usability of Smart City applications - Santos, Felipe; Fonseca, Liliane; Soares, Sérgio; França, Rodrigo; Lemos, Barbara (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2023: Anais do XXII Simpósio Brasileiro de Qualidade de Software, 2023)
Effective assessments are essential for producing reliable results, which, in turn, facilitate a deeper understanding of the subject under investigation. For researchers in the field of Software Engineering (SE), robust assessment strategies play a pivotal role in advancing existing technologies and gauging the suitability of emerging ones. In today’s interconnected world, characterized by the proliferation of smart cities, creating a comprehensive usability assessment plan for smart city applications has posed a unique challenge, primarily due to the multifaceted nature of this paradigm. Aims: The primary objective of this study is to develop and introduce a tool that aids evaluators, mainly novices in usability, in crafting a comprehensive usability assessment plan for smart city applications. This tool aims to encompass all essential elements necessary for a thorough evaluation of the usability of such applications. Method: The instrument is a checklist designed in conformity with experimental best practices and based on experts’ experience in planning and conducting assessments. It was evaluated by experts in assessment planning and has been undergoing a case study of a middleware platform for smart city application development. Results: The use of the instrument aids in the planning of usability assessments of smart city applications, therefore contributing to adapting the usability assessment to the context of a smart city. Conclusions: Even though it is not possible to determine the success of the assessment by using the checklist on its planning, the instrument seeks to encompass the relevant usability points and guide the assessment toward the smart city aspect of the application.